2022
DOI: 10.1108/jocm-03-2022-0061
|View full text |Cite
|
Sign up to set email alerts
|

Fit for functional differentiation: new directions for personnel management and organizational change bridging the fit theory and social systems theory

Abstract: PurposeThis conceptual paper seeks to bridge two existing theories in a bid to broaden our analytical scope when studying the process of onboarding, retention and exclusion of organizational members. The purpose of this paper is to address this issue.Design/methodology/approachThe authors draw on the social systems theory to advance the fit theory demonstrating the pertinence of macro social factors for the determination of person–organization (P–O) fit.FindingsThe result of this conceptual groundwork is a fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…As recent studies have shown, Luhmann's framework is thus well suited for the analysis of specific organizations and how they develop structures for their change (see, e.g. Andersen and Pors, 2022;Andersen and Stenner, 2020;Lies, 2020;Roth et al, 2018;Sales et al, 2022). In particular, these studies demonstrate the analytical potential in the distinction between operation and structure for studying how an organizational system changes.…”
Section: Theorizing Organizational Change Structuresmentioning
confidence: 86%
See 1 more Smart Citation
“…As recent studies have shown, Luhmann's framework is thus well suited for the analysis of specific organizations and how they develop structures for their change (see, e.g. Andersen and Pors, 2022;Andersen and Stenner, 2020;Lies, 2020;Roth et al, 2018;Sales et al, 2022). In particular, these studies demonstrate the analytical potential in the distinction between operation and structure for studying how an organizational system changes.…”
Section: Theorizing Organizational Change Structuresmentioning
confidence: 86%
“…Andersen and Pors, 2022; Andersen and Stenner, 2020; Lies, 2020; Roth et al. , 2018; Sales et al. , 2022).…”
Section: Theorizing Organizational Change Structuresmentioning
confidence: 99%
“…The healthcare sector in Nigeria, though not directly related to renewable energy, provides another perspective on the carbon footprint and its impact on climate change. (Al-Mansur et al, 2023) highlight the significant reliance of Nigerian healthcare facilities on fossil fuels due to inconsistent electrical power supply2. This reliance underscores the urgent need for a shift towards renewable energy sources, aligning with broader objectives of reducing greenhouse gas emissions and combating climate change.…”
Section: Aligning Change With National and Sectoral Goalsmentioning
confidence: 99%